PENGARUH LETHAL SERBUK DAUN MINDI (Melia azedarach L.) TERHADAP KUMBANG JAGUNG (Sitophilus zeamais M.) - Rizal, Syamsul (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
Investigation on lethal effect of leaf Mindi (Melia azedarach L.) to mortality of maize weevil (Sitophilus zeamais M.) was conducted on October 2012 in Laboratory of Biology Faculty of Mathematics University of PGRI Palembang. Acute toxicity test using the maize weevil bioassay method with a time of 96 hours of application.The results shows that leaf of Mindi (Melia azedarach L.) were toxic to maize weevil (Sitophilus zeamais M) with 24 h, 48 h and 96 h LC50 were 29,50%, 21,42%, and 18,0% respectively. Key words: Acute toxicity, Melia azedarach L., Sitophilus zeamais M